KOMPOSISI MAKANAN ALAMI BERBAGAI JENIS TERIPANG DARI PERAIRAN NATUNA KEPULAUAN RIAU - Sukmiwati, Mery (Fakultas Perikanan dan Kelautan Universitas Riau, 2012)
The aim of this research is to investigate natural food composition of varioussea cucumber. Samples were collected in the coastal waters of Natuna, Riau Islandsin June 2009. Samples were taken from 2 location: Sepempang dan Pengadah beach.The analysis methods use is identification of phytoplankton, frequency of presencephytoplankton and percentage volume of phytoplankton. Of ten10 species found 19genus and detritus, include two families : Chrysophyta and Chyanophyta. The highestfrequency of presence is 100% by detritus from Sepempang and Pengadah beach.Thehighest percentage volume of food is 13,5% by Cymbella from Sepempang beachand 13,6% by Cymbella from Pengadah beach.